Fever of Unknown Origin in Children: A 6 year- Experience in a Tertiary Pediatric Egyptian Hospital - Hassan, Rasha H; Fouda, Ashraf E; Kandil, Shaimaa Mohamed AbouZeid (International Journal of Health Sciences, 2014)
<!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE AR-SA MicrosoftInternetExplorer4 <![endif]--> Background: Fever of unknown origin (FUO) is among the most conditions which poses challenge in diagnosis. The presence of information on regional patterns of FUO will shorten the time for diagnosis and reduces health services costs. There are almost no previous studies describing the etiology of FUO in children of Egypt or nearby countries. Aim of the Study: To determine different causes of FUO and the possible diagnostic procedures. Methods: Data of patients with FUO, presented to the Infectious Diseases Unit of Mansoura University Children Hospital, were retrospectively collected in a 6 year-period from May 2006 to May 2011. The study included children with a fever of 38.3° C or more documented by a health care provider and for which the cause could not be identified after 3 weeks of evaluation as an outpatient or after a week of evaluation in hospital. Patients were then categorized into 5 groups. Results: 127 patients met the diagnostic criteria. Infectious diseases were the commonest causes of FUO in 46 cases (36.22%) followed by the miscellaneous causes in 38 cases (29.9%). Meanwhile, collagen vascular diseases and malignancy were diagnosed in 13 cases (10.2%) and 10 cases (7.87%) respectively. While, 20 cases (15.75%) remained undiagnosed. Conclusions: Infectious diseases are the commonest cause of FUO. The delay in diagnosis was due to atypical presentations or inappropriate use of antibiotic prior to the referral. Non infectious causes, malignancy and collagen or vascular disorders were diagnosed in rest of the patients. However, about 15% of our patients remained undiagnosed. The diagnosis was established by non-invasive means in more than two-third of the cases. <!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]-->